2016
DOI: 10.1002/jemt.22635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser preparation on adhesion of a self‐adhesive flowable composite resin to primary teeth

Abstract: The aim of the study was to evaluate the adhesion of a self-adhering flowable composite resin to primary tooth enamel and dentin after silicon carbide paper (SiC) and laser pretreatment. Adhesive properties were evaluated as shear bond strength (SBS) and scanning electron microscopic (SEM) characteristics. A total 120 primary canine teeth were randomly divided into two groups to study enamel and dentin. Each group was divided into 6 subgroups (n = 10) according to type of surface preparation (SiC or Er:YAG las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Thus, it seems that the tooth surface should be prepared with other methods. Similarly, Memarpour et al 22 showed that the use of all-inone OptiBond enhanced the shear bond strength of the self-adhering composite to primary enamel and dentin. Shafiei and Saadat 23 showed that phosphoric acid etching for 15 seconds significantly increased the bond strength to the self-adhering composite.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, it seems that the tooth surface should be prepared with other methods. Similarly, Memarpour et al 22 showed that the use of all-inone OptiBond enhanced the shear bond strength of the self-adhering composite to primary enamel and dentin. Shafiei and Saadat 23 showed that phosphoric acid etching for 15 seconds significantly increased the bond strength to the self-adhering composite.…”
Section: Discussionmentioning
confidence: 91%
“…Erbium laser irradiation creates an irregular rough surface, which is ideal for bonding to composites and is comparable to etched surfaces. 22 However, Jaberi Ansari et al 24 suggested further etching of surfaces treated with the Er,Cr:YSGG laser with phosphoric acid to increase the µSBS to composites. Similar to our study, Memarpour et al 22 used primary enamel samples and applied lasers for their surface treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomena is termed as laser etching (Martinez‐Insua et al, ). Nevertheless the effectiveness of this technique is controversial; while some researchers support the preparation or etching ability of laser to enamel (Basaran et al, ; Kameyama et al, ; Memarpour et al, ; Ozer et al, ; Shafiei et al, ), others deny its efficacy (Martinez‐Insua et al, ; Usumez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have also confirmed this finding. [24][25][26][27][28] Lasing the enamel surface with erbium lasers creates an irregularly rough surface and allows the penetration of adhesive resin into these porosities and undercuts, resulting in the formation of resin tags and subsequent increased micromechanical retention. Previous studies suggested surface roughening by laser irradiation as an alternative to acid etch technique.…”
Section: Discussionmentioning
confidence: 99%